If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + c = 13 Solving 24 + c = 13 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + c = 13 + -24 Combine like terms: 24 + -24 = 0 0 + c = 13 + -24 c = 13 + -24 Combine like terms: 13 + -24 = -11 c = -11 Simplifying c = -11
| x-y+12=0 | | 154=10(15.4+-0.3y)+3y | | 9-6x=7x-95 | | 8+6(3-2n)=20-6n | | 1.4+t=-3.6 | | x^3y-5xy=3x+1 | | 3+x+2=9 | | 839=64 | | 154=10x+3y | | Z+8=y | | 2x+3=5x+1y | | 20+2h=5(17h-10)-13 | | 6+6r=7r | | 8+2x=-6x+104 | | 61*25=x | | 1-10a+8a= | | 3(9t-16)=17t+12 | | (n-2)(2n+5)=0 | | 1+4k=-15 | | 3+5=5x-2 | | 9(5u+2)+12u=5(12u-3) | | f-6.1=-4.3 | | 4*36=X | | x-0.6x=312 | | 8x^2-42x-176=0 | | n-20=15 | | -10+6(0)= | | 4(0)+10= | | 12x=11x+15 | | -3-8n=-4n-3n | | 3+2c=9+c | | P(x)=x^2+5x+6 |